2012
DOI: 10.1111/j.1750-2659.2012.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of clinical case definitions for influenza surveillance among hospitalized patients: results from a rural community in North India

Abstract: Objective:  Clinical case definitions used for influenza surveillance among hospitalized patients vary and need systematic evaluation. Design, setting and sample:  During July 2009–August 2011, we collected clinical data and specimens (nasal and throat swabs) from rural patients hospitalized for acute medical illnesses. Specimens were tested by rRT‐PCR for influenza viruses. Main outcome measures:  Case definitions evaluated the following: influenza‐like illness (ILI: measured fever plus cough or sore throat);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 16 publications
4
30
1
Order By: Relevance
“…27,28 The sensitivities (69-70%) and specificities (43-53%) recorded for the case definition for influenza-like illness in the present study are similar to the corresponding sensitivities (73-78%) and specificities (49-65%) recently reported in northern India, in a study that used the same broad enrolment criteria. 27 However, the same case definition appeared less sensitive but more specific when investigated in Kenya, in a study confined to patients with acute respiratory illness. 28 In the present study, 13% of the hospitalized patients aged < 5 years and 22% of those aged ≥ 5 years were found PCR-positive for influenza viruses.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…27,28 The sensitivities (69-70%) and specificities (43-53%) recorded for the case definition for influenza-like illness in the present study are similar to the corresponding sensitivities (73-78%) and specificities (49-65%) recently reported in northern India, in a study that used the same broad enrolment criteria. 27 However, the same case definition appeared less sensitive but more specific when investigated in Kenya, in a study confined to patients with acute respiratory illness. 28 In the present study, 13% of the hospitalized patients aged < 5 years and 22% of those aged ≥ 5 years were found PCR-positive for influenza viruses.…”
Section: Discussionsupporting
confidence: 73%
“…Very few published studies have evaluated influenza case definitions among hospitalized patients with a similarly broad spectrum of acute illness, including non-respiratory illness. 17,27 Although WHO's case definition for severe acute respiratory illness has frequently been used to screen for influenza among hospitalized patients, our findings indicate that the use of this case definition (both among hospitalized children aged < 5 years and among older hospitalized patients) results in a low detection of influenza cases, although those meeting the case definition are likely to harbour an influenza virus. Similarly low sensitivities have been recorded for this case definition in other studies, at least among patients aged ≥ 5 years.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…However, only 8% of patients in our study reported receiving influenza vaccine, consistent with limited data on uptake in other high‐risk groups in India . Our findings, along with emerging data on influenza virus circulation and influenza‐associated hospitalization incidence in other parts of India, suggest that influenza is a substantial contributor to severe respiratory illness in India and that recommendations for influenza vaccination in certain high‐risk groups may be warranted.…”
Section: Discussionsupporting
confidence: 80%
“…In a previous analysis from the same study, we showed that the sensitivity of original WHO ILI case definition was 78% in Ballabgarh and 87% in Vadu and we would accordingly underestimated the burden had we used the ILI case definition to estimate influenza-associated hospitalization incidence in our study. 17,18 The observed differences in influenza-associated hospitalization incidences between sites in our study could have been partially explained by differences in influenza circulation and transmission. Data from influenza sentinel surveillance conducted at Delhi, the closest city to Ballabgarh, and Pune, the closest city to Vadu, consistently indicated higher levels of influenza virus detection during our study period suggesting that there were true differences in influenza virus circulation and transmission between northern and western India during this time.…”
Section: Discussionmentioning
confidence: 72%